2013
DOI: 10.14233/ajchem.2013.13959
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Determination of Cefixime in Pure Form and in Syrian Pharmaceuticals Through Complexation with Cu(II)

Abstract: Spectroscopic analytical study for the determination of cefixime in pure and its Syrian pharmaceutical formations through complexation with Cu(II) in acetate buffer at pH = 7.8 has been developed. The method is based on the formation pink colour complex between cefixime and Cu(II). The maximum absorbance of the coloured complex occurred at λ = 546 nm and the molar absorptivity is 3.28 × 10 3 L mol-1 cm-1. The reaction conditions have been optimized to obtain the complex. Under optimum conditions the absorbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Many analytical and bioanalytical methods have been reported for the analysis of cephalosporins [19,20]. Cephalosporins have been analysed by complexing these antibiotics with; palladium (II) chloride, copper II chelation, Zinc II complexation and parachloranilic acid complexation [21][22][23][24]. Many HPLC methods have also been introduced for the analysis of cephalosporins [25].…”
Section: Introductionmentioning
confidence: 99%
“…Many analytical and bioanalytical methods have been reported for the analysis of cephalosporins [19,20]. Cephalosporins have been analysed by complexing these antibiotics with; palladium (II) chloride, copper II chelation, Zinc II complexation and parachloranilic acid complexation [21][22][23][24]. Many HPLC methods have also been introduced for the analysis of cephalosporins [25].…”
Section: Introductionmentioning
confidence: 99%
“…The validity of the developed methods was proven by statistical regression line [32], and it was found that percentage relative standard deviation (% RSD) was small while correlation coefficient values (r) were high (table 9) indicating the good linearity of calibration plots. The proposed method's accuracy could be demonstrated by comparing the obtained results with those obtained by comparison methods [33] showing good agreement between them ( II and III, these changes involve wavelength (±2 nm) and temperature results presented in tables 4 to 6. These small changes which can occur during the experimental process didn't influence the absorbance of the studied drugs, demonstrating the robustness of these methods.…”
Section: Resultsmentioning
confidence: 61%
“…Various analytical methods have been reported for analysis of cefixime and other antibiotics after complexation and derivatization with a variety of chemical reagents (Sayed et al, 2013, El-Shaboury et al, 2007, Wani and Patil, 2013, Ahmed et al, 2011, Adegoke and Quadri, 2012, Adegoke and Umoh, 2009). These methods involve spectrophotometric methods (Thakkar and Mashru, 2012, Azmi et al, 2013, Ethiraj et al, 2012, Attimarad et al, 2012, Ramadan et al, 2013, Shah and Kilambi, 2006, Agbaba et al, 1997, El-Wailily et al, 2000), voltammetric method (Rajeev et al, 2010), capillary electrophoresis (Ahemed, 2013), clinical studies (Khan et al, 2008), flow injection spectrophotometry (Abass et al, 2011), HPLC/tandem mass spectrometry (Ronaldo et al, 2001), UPLC/HPLC & IPLC (Ion-Pairing Liquid Chromatography) (Uslu and Ozden, 2013, Manna and Valvo, 2004), alternative continuous infusion method (Hiroyuki et al, 2006) and attenuated total reflectance (ATR) fourier transform infrared (FT-IR) spectroscopy (Kandhro et al, 2013). Among these techniques, UV/Vis spectrophotometry is considered as one of the most widely used technique for determination of cefixime after derivatization (Sayed et al, 2013, El-Shaboury et al, 2007, Wani and Patil, 2013, Ahmed et al, 2011, Adegoke and Quadri, 2012, Adegoke and Umoh, 2009, Thakkar and Mashru, 2012, Azmi et al, 2013, Ethiraj et al, 2012, Attimarad et al, 2012, Ramadan et al, 2013, Shah and Kilambi, 2006, Agbaba et al, 1997, El-Wailily et al, 2000, Rajeev et al, 2010, Ahemed, 2013, Al-Momani, 2001).…”
Section: Introductionmentioning
confidence: 99%